Using coal flotation waste as a heat-insulating billing for the head part of a forging ingot - Ibraev, I.K.; Ibraeva, O.T.; Aitkenov, N.B.; Sakipov, K.E. (Eurasian Physical Technical Journal, 2024)
The experience of using coal flotation waste as a weakly exothermic insulating backfill for insulating the head part of forging dead-melted steel ingots is presented. It has been shown that when using weakly exothermic fills based on single-component fills in the form of coal flotation waste, it is possible to reduce the chemical heterogeneity of the ingot by producing a closed shrinkage cavity, which allows halving heat loss and depth of penetration of shrinkage looseness into the body of the ingot, reducing the segregation of impurities, compacting the head part of the ingot and increasing the yield; moreover, the profitable part of the ingot is more dense and less contaminated with nonmetallic inclusions. The studied patterns of the formation of a closed shrinkage cavity with a dense “bridge” in the head part of a dead-melted steel ingot made it possible to develop and implement a technology for casting large forging ingots of sufficiently high quality using weakly exothermic heat-insulating materials based on metallurgical waste (coke screenings, coal flotation waste).
Keywords: shrinkage cavity; heat-insulating backfill; ingot; dead-melted steel; coal flotation waste; segregation